Developing a Framework of Improved Decision Usefulness in Financial Information - Qizam, Ibnu (E-Jurnal Akuntansi; Vol 31 No 5 (2021), 2021)
It is indispensable to improve decision usefulness for decision-making process for business. This study attempts to seek a framework of expanding a concept of decision usefulness (DU) through a regulatory-process check and a review of financial information literature and the extent to which future research opportunities could emerge from this DU concept for the improved decision usefulness (IDU). The regulatory process and research trends on financial information show that financial-information decision has evolved from reliability-driven to relevance-driven financial-information theories and moves forward to international accounting standardization issues. To this end, the development of ‘synthesis’ theories and approaches in financial information offers many future empirical-study chances for improved decision usefulness. Keywords: Decision Usefulness; Financial Information; Reliability-Driven Financial Information; Relevance-Driven Financial Information; International Accounting Standardization.